Multi-Compartmental Dissolution Method, an Efficient Tool for the Development of Enhanced Bioavailability Formulations Containing Poorly Soluble Acidic Drugs - Miklós Tamás Katona; Lili Nagy-Katona; Réka Szabó; Enikő Borbás; Péter Tonka-Nagy; Krisztina Takács-Novák (MDPI AG, 2023)
The purpose of this study was to investigate the applicability of the Gastrointestinal Simulator (GIS), a multi-compartmental dissolution model, to predict the in vivo performance of Biopharmaceutics Classification System (BCS) Class IIa compounds. As the bioavailability enhancement of poorly soluble drugs requires a thorough understanding of the desired formulation, the appropriate in vitro modelling of the absorption mechanism is essential. Four immediate release ibuprofen 200 mg formulations were tested in the GIS using fasted biorelevant media. In addition to the free acid form, ibuprofen was present as sodium and lysine salts in tablets and as a solution in soft-gelatin capsules. In the case of rapid-dissolving formulations, the dissolution results indicated supersaturation in the gastric compartment, which affected the resulting concentrations in the duodenum and the jejunum as well. In addition, a Level A in vitro-in vivo correlation (IVIVC) model was established using published in vivo data, and then the plasma concentration profiles of each formulation were simulated. The predicted pharmacokinetic parameters were consistent with the statistical output of the published clinical study. In conclusion, the GIS method was found to be superior compared to the traditional USP method. In the future, the method can be useful for formulation technologists to find the optimal technique to enhance the bioavailability of poorly soluble acidic drugs.